Dependence of band structure and carrier concentration of metallic (13, 13) and semiconducting (13, 0) single wall carbon nanotube on temperature - J. Karamdel (Universiti Kebangsaan Malaysia, 2010)
The electronic band structure, density of states (DOS) and carrier concentration of a (13,13) metallic and a (13,0) semiconducting Single Wall Carbon Nanotube (SWCNT) have been estimated and simulated by using the Fermi-Dirac distribution function. The energy dispersion E(k) relation for metallic SWCNT near the minimum energy is linear and the Fermi level was independent of temperature (T). On the other hand for semiconducting SWCNT the E(k) relation is parabolic. The normalized Fermi-Energy (EF – EC) in the nondegenerate regime is a weak (logarithmic) function of carrier concentration and varies linearly with T. In the degenerate condition, the Fermi level was independent of T and was a strong function of carrier concentration.